Contribution of voriconazole N‐oxide plasma concentration measurements to voriconazole therapeutic drug monitoring in patients with invasive fungal infection. Issue 5 (5th February 2023) - Boglione‐Kerrien, Christelle; Morcet, Jeff; Scailteux, Lucie‐Marie; Bénézit, François; Camus, Christophe; Mear, Jean‐Baptiste; Gangneux, Jean‐Pierre; Bellissant, Eric; Tron, Camille; Verdier, Marie‐Clémence; Lemaitre, Florian
Abstract: Background: Voriconazole (VRC), a widely used triazole antifungal, exhibits significant inter‐ and intra‐individual pharmacokinetic variability. The main metabolite voriconazole N‐oxide (NOX) can provide information on the patient's drug metabolism capacity. Objectives: Our objectives were to implement routine measurement of NOX concentrations and to describe the metabolic ratio (MR), and the contribution of the MR to VRC therapeutic drug monitoring (TDM) by proposing a suggested dosage‐adjustment algorithm. Patients and Methods: Sixty‐one patients treated with VRC were prospectively included in the study, and VRC and NOX levels were assayed by LC–MS/MS. A mixed logistic model on repeated measures was implemented to analyse risk factors for the patient's concentration to be outside the therapeutic range. Results: Based on 225 measurements, the median and interquartile range were 2.4 μg/ml (1.2; 4.2), 2.1 μg/ml (1.5; 3.0) and 1.0 (0.6; 1.9) for VRC, NOX and the MR, respectively. VRC Cmin <2 μg/ml were associated with a higher MR during the previous visit. MR values >1.15 and <0.48 were determined to be the best predictors for having a VRC Cmin lower than 2 μg/ml and above 5.5 μg/ml, respectively, at the next visit. Conclusions: Measurement of NOX resulted useful for TDM of patients treated with VRC. The MR using NOX informed interpretation and clinical decision‐making and is very interesting for complex patients. VRC phenotyping based on the MR is now performed routinely in our institution. A dosing algorithm has been suggested from these results.